Risk mitigation action of sport shoes supply chain using the House of Risk Method - Ulfah, Maria; Trenggonowati, Dyah Lintang; Muharni, Yusraeni; Herlina, Lely (Universitas Sultan Ageng Tirtayasa, 2023)
PT PWI, a foreign capital company from South Korea, specializes in manufacturing Adidas and Reebok brand sports shoes. Throughout its supply chain activities, the company often faces challenges and risks, particularly delays in raw material deliveries from suppliers, which can significantly disrupt the production process. Hence, implementing risk mitigation actions becomes essential to alleviate these risks within the supply chain flow. This study aims to identify potential risk events and their agents, proposing strategies for risk mitigation. The House of Risk (HOR) method is employed, while the determination of business process criteria relies on the dimensions of the Supply Chain Operation Reference (SCOR). The study's outcomes include various risk mitigation measures, such as preparing backup suppliers, establishing agreements with suppliers (including compensation costs), implementing regular machine maintenance, enforcing stricter employee supervision, conducting more routine employee briefings, incorporating silica gel into each shoe, applying anti-mold spray to every shipment, implementing new rules for material retrieval using receipts, and enhancing raw material ordering plans and scheduling.